1997
DOI: 10.1074/jbc.272.4.2300
|View full text |Cite
|
Sign up to set email alerts
|

Energy Coupling, Turnover, and Stability of the F0F1 ATP Synthase Are Dependent on the Energy of Interaction between γ and β Subunits

Abstract: Replacement of the F 0 F 1 ATP synthase ␥ subunit Met-23 with Lys (␥M23K) perturbs coupling efficiency between transport and catalysis (Shin, K., Nakamoto, R. K., Maeda, M., and Futai, M. (1992) J. Biol. Chem. 267, 20835-20839). We demonstrate here that the ␥M23K mutation causes altered interactions between subunits. Binding of ␦ or ⑀ subunits stabilizes the ␣ 3 ␤ 3 ␥ complex, which becomes destabilized by the mutation. Significantly, the inhibition of F 1 ATP hydrolysis by the ⑀ subunit is no longer relieved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
104
1

Year Published

1998
1998
2008
2008

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 64 publications
(115 citation statements)
references
References 44 publications
10
104
1
Order By: Relevance
“…We also point out that effects on the thermodynamic parameters of catalysis are easily missed if the level of wild-type and mutant activity happen to coincide near the assay temperature. For example, the ATPase activity of γM23K F " is the same as that of wild-type F " at 21 mC; however, the ∆H ‡ of the γM23K enzyme is 22 kJ\mol greater [43].…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…We also point out that effects on the thermodynamic parameters of catalysis are easily missed if the level of wild-type and mutant activity happen to coincide near the assay temperature. For example, the ATPase activity of γM23K F " is the same as that of wild-type F " at 21 mC; however, the ∆H ‡ of the γM23K enzyme is 22 kJ\mol greater [43].…”
Section: Discussionmentioning
confidence: 92%
“…For a given reaction series that uses the same transition state there should be a quantitative relationship between enthalpy and entropy of activation, such as an isokinetic relationship [54]. We previously demonstrated that the transitionstate thermodynamic parameters from ATP synthases with a variety of mutations or from different sources could be fitted to an isokinetic line [43,45] such as that shown in Figure 5. In isokinetic relationships there is a linear free-energy relationship between two rate constants (k " and k # ) measured at two temperatures (T # T " ), which can be given by the equation : log k # l ajb log k " where a and b are constants [54].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations